Parental Involvement in the English as Foreign Language Class at an Inclusive Primary School in Denpasar - I Dewa Ayu Made Mutiara Lestari; Ni Nyoman Padmadewi; Ni Komang Arie Suwastini (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
Parental involvement in inclusive school is crucial for the development of children with special needs. Thus, the present study observed an inclusive primary school in Denpasar to identify the types of parental involvement in the school, the school's programs to involve parents, and the challenges faced by the teachers in involving parents in their children's education. Following Miles' and Huberman's (1994) model of Interactive Qualitative Data Analysis combined with Epstein's et al. (2002) types of parental involvement at school, the present study revealed that 1) all the six types of parental involvement’s in Epstein’s model were identified with an average of moderate frequency; 2) Seven programs were designed to involve the parents, namely, parenting seminar, class conference, WhatsApp Group discussion, Guest teacher, interactive project, field trip, and collaboration with English-speaking community; 3) there were moderate challenges in involving parents in communicating with the schools, in decision making, and in enrolling the parents in the school activities. This implies that there should be more deliberate effort from the parents in inclusive schools to be more involved in their children’s education, while schools should relentlessly initiate and inspire more intensive parental involvements in the schools’ program.